Synthesis and characterization of aminosilane-coated superparamagnetic iron oxide nanoparticles (SPIONs) - Markiewicz, Karolina; Rynkiewicz, Justyna; Niemirowicz, Katarzyna; Wilczewska, Agnieszka Z. (Видавництво Львівської політехніки, 2011)
Magnetic nanoparticles coated with diverse aminosilane shells were synthesized. The size, structure and chemical composition of the nanoparticles were determined by various techniques, including transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR) and differential scanning calorymetry (DSC). These results are valuable for assessing the future applications of such magnetic silica nanospheres in biomedicine.
Keywords: magnetic nanoparticles; superparamagnetism; core-shell structure; surface coating; aminosilane